Processing of Angelica ( Angelica sylvestris L.) into a functional jam with addition of carob and cinnamon extracts: Evaluation of sensorial, physicochemical, and nutritional characteristics and in vitro bioaccessibility of phenolics - Koç Alibaşoğlu, Elif; Acoğlu Çelik, Büşra; Ceylan, Fatma Duygu; Özoğlu, Özüm; Bekar, Ertürk; Çapanoğlu, Esra; Tamer, Canan Ece; Korukluoğlu, Mihriban; Çopur, Ömer Utku; Yolci Ömeroğlu, Perihan (Wiley, 2024)
Abstract A traditional Angelica jam has been produced from stems of Angelica sylvestris L. growing at the foot of Mount Uludag in Bursa for many years. The aim of this study was to develop new functional formulations of Angelica jam by adding carob and cinnamon extracts, and to evaluate the effect of jam processing and the extracts' addition on the sensory attributes, physicochemical and nutritional characteristics of Angelica jams as well as in vitro bioavailability of phenolics. The main physicochemical properties of the jams including total water‐soluble dry matter (Brix value), pH, invert sugar content, total dietary fiber content, and 5‐(hydroxymethyl) furfural (HMF) ranged between 71.80–72.70 °Bx , 3.65–3.91, 39.30%–49.60%, 0.70–0.90 g/100 g, and 91.00–105.50 mg/kg, respectively. The most abundant minerals were potassium (K), calcium (Ca), magnesium (Mg), phosphorus (P), and iron (Fe) within a concentration range of 80.49–388.67 mg/kg, 111.10–135.00 mg/kg, 24.00–43.28 mg/kg, 7.57–28.06 mg/kg, and 0.52–1.14 mg/kg, respectively. Sensory analysis revealed that general acceptability of Angelica jams in a 9‐point hedonic scale was above 7. The highest antioxidant capacity values of Angelica jam and its functional forms fortified with carob and cinnamon extracts were obtained as 96.68 ± 11.30 mg TE/100 g DM, 248.49 ± 17.78 mg TE/100 g DM, and 193.11 ± 16.06 mg TE/100 g DM, respectively, with the ABTS (2,2′‐azino‐bis‐3‐ethylbenzothiazoline‐6‐sulfonic acid) method. It was observed that the main phenolic compound of the jams was caffeic acid. Depending on the type of extract added into the formulations, trans‐cinnamic acid and gallic acid (GA) became predominant phenolics. Total antioxidant capacity (TAC) of Angelica sylvestris stem decreased by 72%–85% with the heat treatment applied during jam processing. While total phenolic content (TPC) and total antioxidant capacity (measured by the DPPH (1,1‐diphenyl‐2‐picrylhydrazyl) method) increased as a result of intestinal digestion of the jam, it was observed that bioaccessibility of most of the phenolic compounds decreased after intestinal digestion of the jams.